PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH HIBRIDA DAN INBRIDA DI KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Rizky Dwi Saputra; Dwi Haryono; Hurip Santoso (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
The purposes of this research are to analize the influencing production factors on the production of hybrid and inbred rice, and know the amount of income and farm income differences between hybrid and inbred rice in Pesawaran Regency. This research was conducted in three villages chosen purposively, namely Sukadadi, Kutoarjo, and Margodadi Villages, from July 2012 to October 2012. The respondents were 62 farmers, consisting of 30 hybrid farmers and 30 inbred farmers. They were chosen by Simple Random Sampling Technique. The research data was included primary and secondary data. The primary data was obtained by interviewing respondents using questionnaires, while the secondary data was obtained by searching various literatures, printed media and some related agencies. The results showed that the influencing production factors on hybrid rice farming in Gedong Tataan District were the land area and seed, whereas the influencing production factors on inbred rice farming were the land area, NPK Phonska fertilizer, and urea fertilizer. Hybrid farming of rice in Gedong Tataan District was profitable with farmers’ average income from rice as Rp 6,840,099.15 per hectare and the inbred rice farming net income received by farmers was Rp 4,867,136.34 per hectare. The R/C ratio on hybrid rice farming was 1.81 and the inbred rice farming was 1.45. There was no significant difference of income between the farmer respondents of hybrid rice and inbred rice farmer respondents. Keywords : factors of production, hybrid, inbred, income